2022
DOI: 10.1186/s13019-022-01965-w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bronchial anastomotic fistula using autologous platelet-rich plasma post lung transplantation

Abstract: Background Bronchial anastomotic dehiscence is considered one of the most catastrophic early airway complications post-transplant. The presence of a partial dehiscence can also cause further complications such as a fistula between the bronchus and the pleural membrane. Platelet-rich plasma (PRP) is known to significantly enhance the healing process and is being used in the treatment of various conditions, however, so far, there are no reports of the use of PRP in the treatment of bronchial anas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For larger defects seen in dehiscence, a covered metallic stent can also be utilized. Platelet rich plasma may be used in small dehiscence to promote healing via the increase of growth factors, collagen and fibroblasts [47]. When conservative measures fail or in patients with severe dehiscence, reanastomosis, and flap bronchoplasty.…”
Section: Anastomotic Dehiscencementioning
confidence: 99%
“…For larger defects seen in dehiscence, a covered metallic stent can also be utilized. Platelet rich plasma may be used in small dehiscence to promote healing via the increase of growth factors, collagen and fibroblasts [47]. When conservative measures fail or in patients with severe dehiscence, reanastomosis, and flap bronchoplasty.…”
Section: Anastomotic Dehiscencementioning
confidence: 99%
“…It contains a variety of biologically active substances, such as cytokines, which promote tissue repair and regeneration [ 28 ]. Siddique et al [ 29 ] reported a case of noncystic fibrobronchiectasis treated with PRP under bronchoscopy. A patient with a bronchial fistula after bilateral lung transplantation was treated with autologous PRP under bronchoscopy twice.…”
Section: Progress Reportmentioning
confidence: 99%